Economics, governance, and politics in the wine market : European Union developments - Gaeta, Davide; Corsinovi, Paola; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
The global wine industry is a continually modifying market impacted by financing, culture, and politics. Economics, Governance, and Politics in the Wine Market analyzes recent developments in European Agriculture policies on wine legislation and market trend orientation between political power and market structure.
Keywords: Wine industry -- Government policy -- European Union countries; Wine industry -- Law and legislation -- European Union countries; Price regulation -- European Union countries